Risk and Return Optimization Using Innovative Financial Modelling - Deepika, Veereedhi V.; Murty, Dr. A. V. N.; Kumar , Gaurav; Ganapathy , S.; Raju , Dr. N. S. V. N.; Miyan , Dr. Rahmuddin (International Journal of Basic and Applied Sciences, 2025)
This paper investigates the relationship between risk and return using innovative financial ‎modelling techniques applied to secondary data. By leveraging historical datasets, including ‎stock prices, trading volumes, and market trends, the study develops predictive models that ‎analyse market dynamics and optimize investment strategies. The secondary data-based ‎approach is chosen due to the availability of high-quality, extensive datasets from reliable ‎sources, such as stock exchanges and financial reports, which are essential for studying long-term trends and volatility. The research employs advanced statistical techniques, machine ‎learning algorithms, and visualization tools to uncover hidden patterns and test hypotheses ‎with precision. The results provide insights into risk-return trade-offs, optimal portfolio ‎allocations, and the impact of market volatility on returns. This methodology not only ensures ‎the robustness of the findings but also offers generalizability, making the results relevant for ‎investors, financial institutions, and policymakers aiming to improve decision-making in ‎dynamic market environments‎.